2014
DOI: 10.1016/j.toxrep.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Ashwagandha ( Withania somnifera) supercritical CO 2 extract derived withanolides mitigates Bisphenol A induced mitochondrial toxicity in HepG2 cells

Abstract: Bisphenol A (BPA) safety aspects on human health are debated extensively for long time. In the present study, we have studied the toxicity induced by BPA at no observed adverse effect level (NOAEL) using HepG2 cells. We report that BPA at 100 nM induced cytotoxicity to HepG2 cells as determined by MTT assay at 0–72 h. The toxicity was result of reduced oxygen consumption and reduced mitochondrial membrane potential associated with decreased ATP production. The BPA treatment resulted in increase of malondialdeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
4
7
0
Order By: Relevance
“…Interestingly, pre-treatment of SH-SY5Y cells with KSM-66 followed by 6-OHDA treatment was able to lower protein glutathionylation within the cells ( Figure 7 ). These results are in agreement with earlier reports on Ashwagandha extract mediated inhibition of glutathionylation formation in in vitro and in vivo studies ( Sood et al., 2018 ; Vidyashankar et al., 2014 ). It has been reported that a mechanism for Ashwagandha protection of neuronal cells was through activation of the Nrf2 pathway ( Hybertson et al., 2019 ; Priyandoko et al., 2011 ).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Interestingly, pre-treatment of SH-SY5Y cells with KSM-66 followed by 6-OHDA treatment was able to lower protein glutathionylation within the cells ( Figure 7 ). These results are in agreement with earlier reports on Ashwagandha extract mediated inhibition of glutathionylation formation in in vitro and in vivo studies ( Sood et al., 2018 ; Vidyashankar et al., 2014 ). It has been reported that a mechanism for Ashwagandha protection of neuronal cells was through activation of the Nrf2 pathway ( Hybertson et al., 2019 ; Priyandoko et al., 2011 ).…”
Section: Discussionsupporting
confidence: 94%
“…Whereas, post-treatment of KSM-66 restored peroxidase activity at 0.5 and 1 mg/ml ( Figure 5 D) showing that KSM-66 increased peroxidase activity in neuronal cells under oxidative stress. In agreement with previous reports in HepG2 and striatum cells, glutathione peroxidase activities were replenished by Ashwagandha under oxidative stress ( Ahmad et al., 2005 ; Vidyashankar et al., 2014 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations